2013
DOI: 10.1002/tox.21909
|View full text |Cite
|
Sign up to set email alerts
|

Pb2+ induced IL‐8 gene expression by extracellular signal‐regulated kinases and the transcription factor, activator protein 1, in human gastric carcinoma cells

Abstract: Divalent lead (Pb(2+) ) is a common industrial pollutant epidemiologically associated with gastric cancers. Pb(2+) was found to promote tumorigenesis, which may include interleukin (IL)-8, a pro-inflammatory chemokine that promotes angiogenesis and tumor metastasis. Given that the gastrointestinal tract is a major route of Pb(2+) exposure, we investigated the ability of Pb(2+) to induce IL-8 expression in gastric carcinoma cells and its underlying mechanism. At a concentration of 0.1 μM, Pb(2+) induced IL-8 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 26 publications
(37 reference statements)
0
33
0
Order By: Relevance
“…Interestingly, divalent cation such as Pb 21 triggered downstream inflammatory gene activation through different mechanisms. IL-8 also can be induced by Pb 21 in human gastric carcinoma cell through the activation of transcription factor AP1 and ERK1/2 pathways (Lin et al, 2013). In addition, epidermal growth factor receptor (EGFR) is an important element in the plasma membrane responsible for transmitting Pb 21 signals to trigger downstream inflammatory cascades .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, divalent cation such as Pb 21 triggered downstream inflammatory gene activation through different mechanisms. IL-8 also can be induced by Pb 21 in human gastric carcinoma cell through the activation of transcription factor AP1 and ERK1/2 pathways (Lin et al, 2013). In addition, epidermal growth factor receptor (EGFR) is an important element in the plasma membrane responsible for transmitting Pb 21 signals to trigger downstream inflammatory cascades .…”
Section: Discussionmentioning
confidence: 99%
“…IL-8 promoter plasmid was derived from previous study (Lin et al, 2013). Briefly, cells were treated with the drug after overnight transfection, and cells were then harvested using cell lysis buffer.…”
Section: Cell Transfection and Luciferase Assaymentioning
confidence: 99%
“…In in vitro studies, both lead and uric acid have been reported to induce the expression of IL-8 via MAPKs and NF-κB signaling pathways (Lin et al 2015; Liang et al 2015). IL-8 is secreted by multiple cell types in response to pro-inflammatory stimuli and serves as a strong chemotactic agent for neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Lead is a heavy metal, which has been widely used for decades in paint, gasoline, water pipes, storage batteries, and many other products (Lin et al 2015). In the last decades, our view on lead toxicity has changed, giving more concern to exposures, previously considered safe.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation